Assessing the Impact of the COVID-19 Pandemic on Student Wellbeing at Universities in the United Kingdom: A Conceptual Analysis - Burns, Danielle; Dagnall, Neil; Holt, Maxine (Frontiers in Education, 2020)
Transitioning into the university environment can be both exciting and stressful for new and returning students alike. The pressure to perform well academically in an increasingly competitive environment, coupled with a vast array of lifestyle changes, can contribute to suboptimal wellbeing. Over recent years, uptake to wellbeing services within universities in the United Kingdom has grown given the concurrent rise in mental health difficulties reported. Higher education students now have to contend with a drastically altered learning landscape, owing to the discovery of novel coronavirus, Sars-Cov-2, otherwise referred to as COVID-19. In the United Kingdom, universities have moved to close their campuses to both students and non-essential staff in an effort to protect them from contracting the virus. The repercussions of these decisions have been monumental for the delivery of teaching, relationships and, importantly, the provision of student services. Ambiguity remains as to how teaching will be delivered for the forthcoming academic year. The uncertainty caused by the pandemic has yet to be considered in terms of student wellbeing and the new, mostly online, environments that students will be expected to navigate without their typical support networks. For the purpose of this paper, the concept of student wellbeing, a population-level term concerned with positive emotions rather than diagnosed mental health conditions, will be considered in relation to the COVID-19 outbreak. The current paper performs a conceptual analysis on student wellbeing in United Kingdom universities with a specific lens on the psychosocial impact of the global COVID-19 outbreak. Given the unprecedented world that students now learn in, considering the impact of the pandemic on psychosocial outcomes delineates the novel challenges that researchers and practitioners must consider when implementing student wellbeing initiatives moving forward.